2019
DOI: 10.3390/molecules24224121
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Conversion of Toxic Resin Acids

Abstract: Organic wood extractives—resin acids—significantly contribute to an increase in the toxicity level of pulp and paper industry effluents. Entering open ecosystems, resin acids accumulate and have toxic effects on living organisms, which can lead to the ecological imbalance. Among the most effective methods applied to neutralize these ecotoxicants is enzymatic detoxification using microorganisms. A fundamental interest in the in-depth study of the oxidation mechanisms of resin acids and the search for their key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 90 publications
(138 reference statements)
0
6
0
Order By: Relevance
“…All recycled products included AA and DHA, and there was a strong connection between DNA-damaging activity, AA, and DHA concentration. Resin acids such as AA and DHA are significant toxins found in paper and pulp mill effluents (Luchnikova et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…All recycled products included AA and DHA, and there was a strong connection between DNA-damaging activity, AA, and DHA concentration. Resin acids such as AA and DHA are significant toxins found in paper and pulp mill effluents (Luchnikova et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the extracts from the R. placenta -degraded heartwood blocks ( Figure 5 ) revealed the presence of hydroxylated stilbene and resin acid derivatives, which have not been previously identified in natural heartwood decayed by brown rot fungi. Hydroxylated derivatives of PS and PSM have been detected in brown rot decayed wood impregnated with a solution of heartwood stilbenes ( Lu et al, 2016 ), while hydroxylated derivatives of DHA have been found in biotransformation experiments of abietic acid and other abietane resin acids using different types of filamentous fungi ( Özşen et al, 2017 ; Luchnikova et al, 2019 ). In this study, the accumulation pattern of the stilbene derivatives mirrored the pattern of initial stilbene degradation until position 5, after which their concentration decreased and no new stilbene derivatives were detected.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike genetically-related steroid biodegradation pathways, [11] the functions of most of the proteins encoded within the dit cluster have yet to be elucidated and sparse mechanistic information is available on the processing of the A ring. [12,13] In the proficient abietane degrader Burkholderia xenovorans LB400, the coding sequences for these O 2 -dependent dit enzymes are upregulated ~3-fold when grown on dehydroabietic acid (DhA). [8] Yet, the most highly upregulated open reading frame (23-fold, BxeC0606, UniProt ID: Q13HD5) encodes an uncharacterized protein of the PF04909 structural superfamily.…”
mentioning
confidence: 99%
“…DhA-OH could also be generated from crude E. coli lysate enriched with recombinant Pa DitZ and purified on preparative scales (Supporting Information). The { 1 H} 13 C NMR spectrum of DhA-OH contains a new resonance at 75 ppm consistent with a hydroxylated carbon atom that was found to be a component of a tertiary alcohol group by DEPT-135 analysis (Figure S4). The 1 H- 13 C HMBC spectrum of DhA-OH (Figure S5) confirms the assignment of this carbon to C(5) as strong correlation is observed to both 19 Me and 20 Me (Table S2; Figures S6-8).…”
mentioning
confidence: 99%